2020
DOI: 10.3390/catal10020235
|View full text |Cite
|
Sign up to set email alerts
|

A Zn-Doped Ba0.5Sr0.5Co0.8Fe0.2O3-δ Perovskite Cathode with Enhanced ORR Catalytic Activity for SOFCs

Abstract: The insufficient oxygen reduction reaction activity of cathode materials is one of the main obstacles to decreasing the operating temperature of solid oxide fuel cells (SOFCs). Here, we report a Zn-doped perovskite oxide Ba 0.5 Sr 0.5 (Co 0.8 Fe 0.2 ) 0.96 Zn 0.04 O 3-δ (BSCFZ) as the SOFC cathode, which exhibits much higher electrocatalytical activity than Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) for the oxygen reduction reaction (ORR). The BSCFZ cathode exhibited a polarization resistance of only 0.23 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Polarization resistances (Rp) at high frequency are attributed to charge transfer processes and Rp at low frequency are attributed to oxygen surface exchange process. [26][27][28] The plot was dominated by a semicircle which was attributed to the surface oxygen reduction reaction on the electrode. The cell with LSC nanofibers displays smaller Rp than LSC powder at same experimental conditions.…”
Section: Electrocatalytic Activity and Stabilitymentioning
confidence: 99%
“…Polarization resistances (Rp) at high frequency are attributed to charge transfer processes and Rp at low frequency are attributed to oxygen surface exchange process. [26][27][28] The plot was dominated by a semicircle which was attributed to the surface oxygen reduction reaction on the electrode. The cell with LSC nanofibers displays smaller Rp than LSC powder at same experimental conditions.…”
Section: Electrocatalytic Activity and Stabilitymentioning
confidence: 99%
“…The ORR is a key process also in solid oxide fuel cells (SOFCs). In this context, Zeng et al [5] reported a Zn-doped perovskite oxide Ba 0.5 Sr 0.5 (Co 0.8 Fe 0.2 ) 0.96 Zn 0.04 O 3-δ (BSCFZ) as the SOFC cathode, which exhibited much higher electrocatalytical activity than Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) for the ORR. An increase in maximum power density by 35% in comparison with the BSCF cathode was recorded in a single cell at 750 • C, attributed to a better balance of oxygen vacancies, surface electron transfer, and ionic mobility as promoted by the low-valence Zn 2+ doping.…”
Section: This Special Issuementioning
confidence: 99%
“…It can be also ascribed to oxygen vacancies, proper ionic mobility, and surface electron transfer that are facilitated by Zn 2+ doping. 19 Even so, of most bulk perovskite oxides, the inferior electrical conductivity 9,31,32 and weak adsorption capacity to oxygen species 33,34 at room temperature still restrict their oxygen electrocatalytic performance. More specifically, the high adsorption energy barrier is not conducive to the formation of active surface adsorbate intermediates of OOH* species.…”
Section: Introductionmentioning
confidence: 99%
“…Among these alternatives, perovskite oxides with a universal ABO 3 formula hold promising prospects to be efficient ORR electrocatalysts. The great flexibility of perovskite oxides in composition and crystal structure implies the adjustability of their intrinsic electronic structure. Doping heteroatoms at A and B sites and designing cation/anion nonstoichiometry deficiencies are considered effective strategies to facilitate the electronic structure and boost their intrinsic activities. Moreover, it is generally believed that tuned oxygen defects and optimized e g -filling of the B-site element can bring about the most favorable catalytic properties of the ORR processes. , Wang et al regulated the electronic structure and intrinsic activity of LaCoO 3 -based perovskites through tuning A-site cation deficiencies accompanied by oxygen vacancy creation . Zeng et al proved that Zn-doped Ba 0.5 Sr 0.5 (Co 0.8 Fe 0.2 ) 0.96 Zn 0.04 O 3−δ (BSCFZ) perovskite oxide exhibited an elevated ORR activity.…”
Section: Introductionmentioning
confidence: 99%